Evaluation of Antidiabetic Effect of Seena occindentalis Flower Extracts On an Experimentally Induced Type 2 Diabetes In Rats - Pathak, Sachchidanand; Chaoubey, Prashant; Pratap, Vijay; Mishra, Anurag; Rawat, Sarita; Tripathi, Shashibhushan (Journal of Neonatal Surgery, 2025)
Aim of this study to identify the activity of Senna occidentalis flower to the antihyperglycaemic activity and hypolipidemic activity using high fat diet-streptozotocin model. Prepare the aqueous ethanolic extract of Senna occidentalis flower 250 and 500 mg/kg dose was used to treat the diabetic rat. Low and high dose of Senna occidentalis flower extract to evaluate the body weight, food consumption and activity of blood glucose level, oral glucose tolerance test, kidney function test, and liver function test up to 39 days. Raised glycosylation of haemoglobin, which has been seen to be increased over a lengthy period of time in diabetes, is present in uncontrolled diabetes which worst’s the condition of this disease. Different finding suggests that the SOFE stimulates beta cells to secrete more insulin. They also found that HFD-STZ-induced diabetic rats treated with low and high doses of SOFE had lower levels of triglyceride, total cholesterol, very low-density lipoprotein, and low-density lipoprotein and higher levels of high-density lipoprotein, implying that elevated insulin levels may be responsible for these changes. Different compounds are found by using the technique infrared, thin layer chromatography, and high-performance thin layer chromatography. Higher dose indicate less reduction in serum glutamic pyruvic transaminase and serum glutamic oxaloacetic transaminase as compare to the lower dose may be higher dose produce the liver toxicity. For further study it is concluded that the low dose is effective for the animals that cause no toxicity and did not affect any other parts of the body.